1999
DOI: 10.1002/(sici)1096-9853(199907)23:8<829::aid-nag16>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Layered elastic model for analysis of Cone Penetration Testing

Abstract: A layered elastic model is adopted in the paper for the analysis of soil layering e!ects on the results of Cone Penetration Testing (CPT). Analytical solutions associated with the layered elastic CPT model and obtained via numerically integrating the fundamental singular solution for layered elastic solids due to the action of a body force concentrated on a circular ring. The soil layering e!ects on the CPT tip and friction resistance are examined in detail using the layered elastic CPT model. These examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…For cone penetration in layered soils, investigations were mostly undertaken for sediments with either surface or interbedded sand layer (e.g. Meyerhof and Valsangkar 1977;Van den Berg 1994;Vreugdenhil et al 1994;Berg et al 1996;Van den Berg et al 1996;Lunne et al 1997;Yue and Yin 1999;Ahmadi and Robertson 2005;Xu and Lehane 2008). In brief, Meyerhof and Valsangkar (1977), Van den Berg (1994) and Xu and Lehane (2008) performed model tests on piles and cone penetrometers in two-and three-layer soils.…”
Section: Previous Workmentioning
confidence: 99%
“…For cone penetration in layered soils, investigations were mostly undertaken for sediments with either surface or interbedded sand layer (e.g. Meyerhof and Valsangkar 1977;Van den Berg 1994;Vreugdenhil et al 1994;Berg et al 1996;Van den Berg et al 1996;Lunne et al 1997;Yue and Yin 1999;Ahmadi and Robertson 2005;Xu and Lehane 2008). In brief, Meyerhof and Valsangkar (1977), Van den Berg (1994) and Xu and Lehane (2008) performed model tests on piles and cone penetrometers in two-and three-layer soils.…”
Section: Previous Workmentioning
confidence: 99%
“…In this study, Vreugdenhil et al (1994) demonstrated that the cone senses the presence of the approaching layer elastically. Yue & Yin (1999) extended this work using rigorous analytical solutions for the static responses of ring type concentrated body forces and examined soil layering effects in both compressible and incompressible soils. Van den Berg et al (1996) presented an Eulerian analysis of the cone penetration test in multi-layered soils.…”
Section: Introductionmentioning
confidence: 99%
“…From 1984 to present, the author has examined the threedimensional boundary-value problems of the classical elasticity in nonhomogeneous and transversely isotropic solid [5,6,[11][12][13][14][15][16][17]19,20,[77][78][79][80][81]. The solid occupies a threedimensional space of an infinite lateral extent ð -1 < x, y < þ 1Þ and a finite thickness a£z£bÞ, a semiinfinite a£z < þ 1Þ, and/or an infinite extent ð -1 < z < þ 1Þ.…”
Section: The Author's Workmentioning
confidence: 99%